Mechanisms underlying TRPV4-mediated regulation of miR-146a expression - Dutta, Bidisha; Mahanty, Manisha; Kesavalu, Lakshmyya; Rahaman, Shaik O. (Frontiers in Immunology, 2024)
Persistent inflammation is a major contributor in the development of various inflammatory diseases like atherosclerosis. Our study investigates how transient receptor potential vanilloid 4 (TRPV4), a mechanosensitive ion channel, interacts with microRNA-146a (miR-146a), within the context of inflammation and atherosclerosis. Micro-RNAs play a critical role in controlling gene expression, and miR-146a is notable for its anti-inflammatory actions. TRPV4 is activated by diverse soluble and mechanical stimuli, and often associated with inflammatory responses in various diseases. Here, we find that TRPV4 negatively regulates miR-146a expression in macrophages, especially following stimulation by lipopolysaccharides or alterations in matrix stiffness. We show that in atherosclerosis, a condition characterized by matrix stiffening, TRPV4 decreases miR-146a expression in aortic tissue macrophages. We find that TRPV4's impact on miR-146a is independent of activation of NFκB, Stat1, P38, and AKT, but is rather mediated through a mechanism involving histone deacetylation instead of DNA methylation at the miR-146a promoter site. Furthermore, we show that N-terminal residues 1 to 130 in TRPV4 is essential in suppression of miR-146a expression in LPS-stimulated macrophages. Altogether, this study identifies a regulatory mechanism of miR-146a expression by TRPV4 which may open new potential therapeutic strategies for managing inflammatory diseases.